2022
DOI: 10.1192/bjo.2022.565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psilocybin versus escitalopram on rumination and thought suppression in depression

Abstract: Background Major depressive disorder is often associated with maladaptive coping strategies, including rumination and thought suppression. Aims To assess the comparative effect of the selective serotonin reuptake inhibitor escitalopram, and the serotonergic psychedelic psilocybin (COMP360), on rumination and thought suppression in major depressive disorder. Method Based on data derived from a randomised clinical trial (N = 59), we performed exploratory analyses on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…The Cochrane RoB 2 tools were used to evaluate the included studies ( table 3 ). RoB 2 for randomised trials was used for the five reports of parallel randomised trials (Carhart-Harris et al 63 and its secondary analysis Barba et al, 64 Goodwin et al 18 and its secondary analysis Goodwin et al, 65 and von Rotz et al 66 ) and RoB 2 for crossover trials was used for the four reports of crossover randomised trials (Griffiths et al, 14 Grob et al, 15 and Ross et al 17 and its follow-up Ross et al 67 ). Supplementary Appendix G provides a detailed explanation of the assessment of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The Cochrane RoB 2 tools were used to evaluate the included studies ( table 3 ). RoB 2 for randomised trials was used for the five reports of parallel randomised trials (Carhart-Harris et al 63 and its secondary analysis Barba et al, 64 Goodwin et al 18 and its secondary analysis Goodwin et al, 65 and von Rotz et al 66 ) and RoB 2 for crossover trials was used for the four reports of crossover randomised trials (Griffiths et al, 14 Grob et al, 15 and Ross et al 17 and its follow-up Ross et al 67 ). Supplementary Appendix G provides a detailed explanation of the assessment of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…49 As a result, it is possible that psychedelics might also have the potential to lessen these negative emotions associated with pain. This is supported by evidence suggesting that psilocybin may mitigate similar affective phenomena, such as depressive rumination and obsessive thinking, 50 which can resemble the fear of movement seen in chronic pain. Given that depressive and anxiety disorders often co-occur with chronic pain, 51 psychedelics may provide a more comprehensive treatment strategy by targeting these affective aspects, which can often be equally hard to discern and equally debilitating for these patients.…”
Section: Impact On Negatively Valenced Emotional States Related To Th...mentioning
confidence: 77%
“…Other clinical study has reported that psilocybin-assisted therapy facilitates psychosocial-spiritual growth in cancer patients (Shnayder et al, 2023). Psilocybin also significantly decreases thought suppression and rumination in patients with major depressive disorder (Barba et al, 2022). It has been reported that oral administration of 10–25 mg psilocybin may be effective for the treatment of PTSD (Krediet et al, 2020).…”
Section: Discussionmentioning
confidence: 99%